A child in shock: carotid blowout syndrome. Issue 3 (10th August 2019) - Stilwell, Philippa Anna; Robertson, Fergus; Bhate, Sanjay; Sutcliffe, Alastair G
Abstract : Paediatricians commonly encounter neck lumps during their routine clinical practice; vascular abnormalities, such as (pseudo)aneurysms, are a rare cause of these. Pseudoaneurysms of the carotid artery in children are usually the result of blunt or penetrating trauma, infection or vasculitis/connective tissue disorders. They can present with a variety of symptoms including neck pain, as a pulsatile neck mass or with compressive symptoms (for example, cranial nerve palsies or dyspnoea). Pseudoaneurysms carry a risk of rupture in which case they are fatal, unless immediate treatment is provided. We report a 17-month-old male child with idiopathic carotid artery blowout syndrome presenting with acute oropharyngeal haemorrhage leading to asystolic cardiac arrest. He was successfully resuscitated and emergency embolisation controlled the bleeding. Despite extensive left hemispheric infarct, he has survived. Carotid artery blowout syndrome needs to be recognised as a potential cause of major haemorrhage in childhood. The purpose of this case report is to remind readers of the differential diagnosis and work-up of a child presenting with a neck lump, to highlight important aspects of the acute management of major haemorrhage and massive blood transfusion in paediatrics, to describe the aetiology, presentation and management of carotid artery pseudoaneurysm in children and to discuss long term rehabilitation in patients with consequent neurological sequelae (including the need for input from multiple specialty teams).